The Accent of Slavic *ja(zъ ) 'I' - Kapović, Mate (2009)
In this article, I have tried to show that the two forms of the Slavic first person nominative singular personal pronoun, *ja and *jazъ , are related to the two different accents attested in Slavic – the neo-acute (for instance in Štokavian dial. jã , Czech já) and the old acute (for instance in Slovene jà z, North Čakavian jȁ (z)). Originally there were two forms in Slavic – *ja̋ and *jã zъ < *jā zъ ̍ . One of the accentual variants was generalized in specific Slavic dialects, thus leading to the present situation. The form *ja̋ is to be derived directly from PIE *éǵ (Lithuanian à š, Avestan azə ) with the acute as the result of Winter’ s Law. The form *jā zъ ̍ is to be derived from PIE *eǵ Hóm (Vedic ahám) with the final accent, and the length is to be explained as the result of Winter’ s Law with the subsequent elimination of the pretonic acute in Slavic. The form *ja̋ did not undergo the operation of Meillet’ s Law, in spite of the mobile paradigm (*mȅ ne, *mь /ъ nẹ ̍ , *mę̑ ), because the stems in question were obviously suppletive (*ja‑ : *m‑ ).
Zbornik radova s konferencije International Workshop on Balto-Slavic Accentology 2 (Kopenhagen 2006)
Projekt MZOS
ENG